2016
DOI: 10.1099/ijsem.0.001543
|View full text |Cite
|
Sign up to set email alerts
|

Arsenicitalea aurantiaca gen. nov., sp. nov., a new member of the family Hyphomicrobiaceae, isolated from high-arsenic sediment

Abstract: A novel arsenic-resistant bacterium, designated 42-50T, was isolated from the high-arsenic sediment of Jianghan Plain, Hubei Province, China. Phylogenetic and biochemical analysis indicated that this bacterium represents the first species of a novel genus belonging to the family Hyphomicrobiaceae. The 16S rRNA gene of strain 42-50T shares 96.3-94.2, 96.3, 96.2 and 94.9-93.8 % sequence identities to those of species from the genera Devosia, Youhaiella, Paradevosia and Pelagibacterium, respectively. The major ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…The polar lipid profile of strain LMO-2 T comprised diphosphatidylglycerol, phosphatidylglycerol, phospholipid and five unknown polar lipids (Fig. S3), which is consistent with the type species of the genera Devosia, Youhaiella, Pelagibacterium and Paradevosia, while the genus Arsenicitalea does not contain any unknown phospholipids [2]. As mentioned above, phylogenetic and genomic analysis suggested that strain LMO-2 T represents a novel genus that is closely to several genera of the family Devosiaceae: including Arsenicitalea [2], Pelagibacterium [4], Devosia [26], Paradevosia [27] and Youhaiella [54].…”
Section: Physiology and Chemotaxonomysupporting
confidence: 69%
See 2 more Smart Citations
“…The polar lipid profile of strain LMO-2 T comprised diphosphatidylglycerol, phosphatidylglycerol, phospholipid and five unknown polar lipids (Fig. S3), which is consistent with the type species of the genera Devosia, Youhaiella, Pelagibacterium and Paradevosia, while the genus Arsenicitalea does not contain any unknown phospholipids [2]. As mentioned above, phylogenetic and genomic analysis suggested that strain LMO-2 T represents a novel genus that is closely to several genera of the family Devosiaceae: including Arsenicitalea [2], Pelagibacterium [4], Devosia [26], Paradevosia [27] and Youhaiella [54].…”
Section: Physiology and Chemotaxonomysupporting
confidence: 69%
“…Growth at various temperatures (5, 10, 15, 20, 25, 30, 35, 40, 45 and 50 °C) and different NaCl concentrations (0, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15 %, w/v) were examined following growth on R2A agar medium. The pH range for growth was measured in R2A broth at various pH values (pH 4.0–12.0 at intervals of 0.5 pH unit) for 7 days by using the buffer systems Na 2 HPO 4 /citric acid (for pH 5.0–7.0), Tris/HCl (pH 8.0–9.0) and Na 2 CO 3 /NaHCO 3 (pH 9.0–11.0), respectively, in R2A broth medium at the concentration of 40 mM [2, 4]. Oxidase activity was determined by using an oxidase reagent kit (bioMérieux).…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sequence alignments were conducted using the ClustalW2 software as described elsewhere ( Zhang et al, 2015 ; Mu et al, 2016a ). A phylogenetic tree of the obtained ArsMs and their closely related homologues was constructed using the maximum likelihood method implemented in MEGA 6.0 as described previously ( Xu et al, 2014 ; Mu et al, 2016b ).…”
Section: Methodsmentioning
confidence: 99%
“…Luteolibacter have previously reported as one of the 5 most abundant genera in arsenic contaminated soil 63 and Devosia were shown to exhibit high sequence similarity to arsenic tolerant organisms isolated from arsenic rich environments. 64 Therefore, both the genomic matches of arsM OTUs and the correlated copy number patterns in Group I, II, III, and IV arsM and genera level 16S rRNA OTUs present potential targets for identification of arsM organisms and the study of arsenic transformation in paddy soil.…”
Section: Environmental Science and Technologymentioning
confidence: 99%